2016
DOI: 10.3390/ijgi5050071
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Traffic Congestion Clustering Judgment Based on Grey Relational Analysis

Abstract: Traffic congestion clustering judgment is a fundamental problem in the study of traffic jam warning. However, it is not satisfactory to judge traffic congestion degrees using only vehicle speed. In this paper, we collect traffic flow information with three properties (traffic flow velocity, traffic flow density and traffic volume) of urban trunk roads, which is used to judge the traffic congestion degree. We first define a grey relational clustering model by leveraging grey relational analysis and rough set th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Finally, the threshold of traffic state discrimination was calibrated by simulation data. Zhang (2016) et al [7] took speed, traffic flow, and traffic density as data sets and defined the relational relationship between multidimensional attribute information based on grey relational analysis and rough set theory, established the grey relational clustering model, and then introduced the grey relational membership ranking algorithm (GMRC) to discriminate the clustering priority, so as to analyze the degree of road network congestion. Shang (2017) et al [8] constructed a traffic state discrimination model based on spectral clustering and stochastic subspace integration K-nearest neighbor (RS-KNN) in order to improve the accuracy of urban expressway traffic state discrimination.…”
Section: The Methods Based On Data Miningmentioning
confidence: 99%
“…Finally, the threshold of traffic state discrimination was calibrated by simulation data. Zhang (2016) et al [7] took speed, traffic flow, and traffic density as data sets and defined the relational relationship between multidimensional attribute information based on grey relational analysis and rough set theory, established the grey relational clustering model, and then introduced the grey relational membership ranking algorithm (GMRC) to discriminate the clustering priority, so as to analyze the degree of road network congestion. Shang (2017) et al [8] constructed a traffic state discrimination model based on spectral clustering and stochastic subspace integration K-nearest neighbor (RS-KNN) in order to improve the accuracy of urban expressway traffic state discrimination.…”
Section: The Methods Based On Data Miningmentioning
confidence: 99%
“…Three papers on ITS are as follows: (1) "Vehicle positioning and speed estimation based on cellular network signals for urban roads," by Lai and Kuo [41]; (2) "A method for traffic congestion clustering judgment based on grey relational analysis," by Zhang et al [42]; and (3) "Smartphone-based pedestrian's avoidance behavior recognition towards opportunistic road anomaly detection," by Ishikawa and Fujinami [43].…”
Section: Intelligent Transportation Systemsmentioning
confidence: 99%
“…The proposed method based on grey relational analysis can obtain the membership degree rank of classes for judging the rank of data objects and improving the accuracy of traffic congestion detection. In experimental environments, the practical traffic flow records were collected from 30 drivers to evaluate the proposed method, and the results showed that the average accuracy of the proposed algorithm was 24.9% higher than that of the K-means algorithm [42].…”
Section: Intelligent Transportation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, grey relational analysis, which is another active branch of grey system theory, has been successfully applied to management science and industrial control in practice [33,34]. Zhang et al [35] used grey relational analysis for traffic congestion clustering judgment and obtained good results.…”
Section: Introductionmentioning
confidence: 99%